Shifts in the portfolio holdings of euro area investors in the midst of COVID-19: Looking-through investment funds - Daniel Carvalho; Martin Schmitz (European Central Bank (ECB), 2021)
We study the impact of the COVID-19 shock on the portfolio exposures of euro area investors. The analysis "looks-through" holdings of investment fund shares to first gauge euro area investors' full exposures to global debt securities and listed shares by sector at end-2019 and to subsequently analyse the portfolio shifts in the first and second quarters of 2020. We show important heterogeneous patterns across asset classes and sectors, but also across euro area less and more vulnerable countries. In particular, we find a broad-based rebalancing towards domestic sovereign debt at the expense of extra-euro area sovereigns, consistent with heightened home bias. These patterns were strongly driven by indirect holdings - via investment funds - especially for insurance companies and pension funds, but levelled off in the second quarter. On the contrary, for listed shares we find that euro area investors rebalanced away from domestic towards extra-euro area securities in both the first and the second quarter, which may be associated with better relative foreign stock market performance. Many of these shifts were only due to indirect holdings, corroborating the importance of investment funds in assessing investors' exposures via securities, in particular in times of large shocks. We also confirm the important intermediation role played by investment funds in an analysis focusing on the large-scale portfolio rebalancing observed between 2015 and 2017 during the ECB's Asset Purchase Programme.
Keywords: F30; F41; G15; 330; Bilateral portfolio holdings; investment funds; cross-border investment; sovereign debt; COVID-19; Coronavirus; Portfolio-Management; Institutioneller Investor; Investmentfonds; Eurozone